Azospirillum as Biofertilizer for Sustainable Agriculture: Azospirillum brasilense AZ39 as a Model of PGPR and Field Traceability - Coniglio, Anahí (2019)
Azospirillum is one of the best studied genus of plant growth promoting rhizobacteria at present. These bacteria are able to colonize hundreds of plant species and significantly improve their growth, development and productivity under field conditions. Besides nitrogen fixation, the most studied mechanism proposed for Azospirillum to explain plant growth promotion of inoculated plants has been related to its ability to produce several phytohormones, mainly auxins and particularly indole-3-acetic acid. Although different capacities have been described to explain the plant growth regulation by Azospirillum one single mechanism is not quite extensive to explain the full effect observed on inoculated plants. The bacterial mode of action is currently better explained as the result of additive and selective effects. One of the most important achievements obtained thus far is the utilization of azospirilla as commercial inoculants in approximately 7.0 million doses and 5.0 million ha, mainly cultivated with cereal crops and legumes in South America. Different inoculation practices (farmer applied or industrial seed treatments, infurrow, foliar or soil sprayed applications) have been developed and improved in the last two decades for a wide range of crops, in field conditions. Particularly, the combined inoculation of legumes with rhizobia and azospirilla, could over improve the performance of the plants compared with a single inoculation, due to the complementary biological processes of both microbes. The development and validation of specific novel methodologies for identification of A. brasilense, and particularly the strain Az39 in both bio-products and inoculated samples (i.e. soil, rhizosphere, seeds or plant tissues) offer a precise tool to evaluate the functionality and traceabilityof these microorganisms in the environment. In this chapter, we explore some classical mechanisms of plant growth promotion in A. brasilense Az39, one of the most widely used PGPR strains for inoculant production in South America. Additionally, we discuss some novel molecular tools designated to identify this strain in both bio-products and field conditions.